In vitro evaluation of the pogostone effects on the expression of PTEN and DACT1 tumor suppressor genes, cell cycle, and apoptosis in ovarian cancer cell line - Mansour Homayoun; Nayereh Sajedi; Mitra Soleimani (Wolters Kluwer Medknow Publications, 2022)
Background and purpose: Ovarian cancer is one of the most dangerous cancers among women. Pogostone has anticancer effects and is rich in polyphenol compounds. In the present study, we investigated the effects of pogostone on ovarian cancer cell lines (OVCAR-3). Experimental approach: OVCAR-3 cells were treated with pogostone at IC50 (90 μg/mL) for 24 and 48 h. Cell viability and apoptotic rate in the cells were measured using MTT assay and flow cytometry. Real-time PCR was used to determine the expression of genes involved in the cell cycle and apoptosis. The expression of caspase-3 (CASP3) protein was evaluated by the CASP3 assay. Findings/Results: Treatment of OVCAR-3 cells with pogostone increased the expression levels of phosphatase and tensin homologue deleted on chromosome ten (PTEN) and Dapper antagonist of catenin-1 (DACT1) tumor suppressor genes, as well as the apoptotic genes CASPs3, 8, and 9. Moreover, the ratio of the expressed BCL2 associated X (BAX)/BCl2 genes, as pro- and anti-apoptotic genes, was increased. The expression levels of the genes related to the cell cycle progression including cyclin D1 (CCND1) and cyclin- dependent kinase 4 (CDK4) were inhibited. The data obtained from flow cytometry indicated that pogostone induced cell apoptosis in 24 and 48 pogostone groups. The CASP3 colorimetric assay revealed that pogostone increased the expression of CASP3 protein in the treated groups. Conclusion and implication: Pogostone, by inducing the expression of PTEN and DACT1 tumor suppressor genes and regulation of downstream genes may decrease cell proliferation and increase the rate of apoptosis in OVCAR-3.